2017
DOI: 10.3233/wor-162475
|View full text |Cite
|
Sign up to set email alerts
|

Safety behavior and work safety climate among landscaping and groundskeeping workers in North Carolina: A pilot study

Abstract: This is the first study of its kind to evaluate work safety climate among landscaping and groundskeeping workers. Although self-reported safety practices were moderate, minority workers described their work safety climate as being poor. As a pilot study, these results suggest that employers of landscaping and groundskeeping workers could do more to improve safety climate within the organization with an emphasis on safety training for minority and underrepresented workers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 21 publications
1
8
1
Order By: Relevance
“…Our results are consistent with research showing Latino/a workers as experiencing the highest rate of fatal occupational injury nationwide 8,18–24 . Workers in southern states, especially those who labor outside, are at special risk of illness due to heat and humidity, especially in agriculture and construction 9,25–29 . Early work on construction safety noted characteristics of the worker, including English‐language proficiency, documentation status, cultural factors, and the desire to appear industrious, as contributors to inequities between groups of workers 30,31 .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our results are consistent with research showing Latino/a workers as experiencing the highest rate of fatal occupational injury nationwide 8,18–24 . Workers in southern states, especially those who labor outside, are at special risk of illness due to heat and humidity, especially in agriculture and construction 9,25–29 . Early work on construction safety noted characteristics of the worker, including English‐language proficiency, documentation status, cultural factors, and the desire to appear industrious, as contributors to inequities between groups of workers 30,31 .…”
Section: Discussionsupporting
confidence: 89%
“…8,[18][19][20][21][22][23][24] Workers in southern states, especially those who labor outside, are at special risk of illness due to heat and humidity, especially in agriculture and construction. 9,[25][26][27][28][29] Early work on construction safety noted characteristics of the worker, including English-language proficiency, documentation status, cultural factors, and the desire to appear industrious, as contributors to inequities between groups of workers. 30,31 Recent work has increasingly focused on the occupational environment surrounding the workers, suggesting that understanding of labor laws and protections available to workers, perceptions by employers that Latino/a workers will accept risky assignments, and poor communication (including by supervisors and coworkers) are likely factors that contribute to inequities in fatal occupational injury between Latino/a and White workers.…”
Section: Discussionmentioning
confidence: 99%
“…Safety education and training provide the knowledge and skills necessary to perform the job safely (Barling et al, 2002; Kinn et al, 2000). Safety researchers suggest strengthening safety-related education and elevating safety climate or perception of risk of injuries to reduce and prevent the occurrence of occupational injuries (Kearney et al, 2017; Schwatka and Rosecrance, 2016; Tao et al, 2017). Safety climate relates to employees’ perceptions of management’s commitment and performance in regard to safety policy, procedures and practice (Maureen and Arnold, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…A survey of the peer-reviewed literature turned up three articles on noise, heat stress, and UV exposures to university groundskeepers in North Carolina; [12][13][14] four articles on injuries and fatalities among landscapers and arborists; [15][16][17][18] one study of fatalities associated with the use of wood chippers, mostly for workers in the landscaping services industry; 19 a study of injuries and illnesses in arborists and gardeners in northeastern Italy; 20 and six surveys or observations of safety knowledge and behaviors among landscapers, groundskeepers, and arborists. [21][22][23][24][25][26] Several studies from related industries and nonoccupational settings were also found.…”
Section: Prior Researchmentioning
confidence: 99%